LEGAL REVIEW OF THE CRIMINAL CASE OF IDENTITY FALSEMENT IN PASSPORT ISSUANCE ( Study Case Decision Palangkaraya District Court Number 402/ Pid.Sus /2020/PN Plk ) - Krisna Wati; Aristoteles; Evi; Claudia Yuni Pramita (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Study This study accountability criminal to perpetrator main and related parties​​ participate as well as in action criminal forgery identity For get Document Journey Republic of Indonesia. The research also examines the role and authority of Immigration PPNS in enforcement law to action criminal immigration of a legal nature inclusion . Research use method juridical normative with approach legislation and studies case to Decision Number 402/ Pid.Sus /2020/PN Plk . Research results show that perpetrator main sentenced criminal based on Article 126 letter c of the Law Number 6 of 2011 concerning Immigration , but other parties are also involved in case This No ensnared criminal Because No made into subject law in investigation , although fact trial show existence parties involved​ and related assistance​​ direct with actions criminal . This is cause problem implementation principle accountability criminal liability and inclusion ( deelneming ) which are not optimal in law immigration . Research This confirm importance implementation principle justice substantive with ensnare all over parties involved​ as well as in action criminal , as well as strengthen the role of Immigration PPNS so that it can uphold law in a way comprehensive and proportional .